Penerapan Metode Pembelajaran Kooperatif Tipe STAD untuk Meningkatkan Hasil Belajar Materi Mahluk Hidup - Firdausi, Rofiqoh; Albar, Melani (Prodi PGMI STAI Al-Akbar Surabaya, 2024)
In general, class 4 learning at MI Manarul Huda Sukoanyar Wajak. In general, students also tend to be passive and less active in learning, only accepting what the teacher says without being able to express opinions, ask and answer questions. If the teacher asks questions, students don't dare to answer. If there are problems students don't dare to ask. The formulation of the problem in this research is (1) How is the implementation of the STAD type cooperative learning method for class IV students at MI Manarul Huda in mastering the material